'It's hard not to be a teacher sometimes': Citizen ethnography in school. Issue 3 (1st August 2013) - McDougall, Julian
This article reflects on a European Union-funded research project – Social Documentary as a Pedagogic Tool – and its local implementation in Citizenship pedagogy in three non-selective English secondary schools in mixed and 'disadvantaged' communities in the West Midlands. An ethnographic methodology (for pedagogy) enabled Citizenship students to produce documentary films representing their communities' perceptions of local identities in relation to Europe and its future. In working ethnographically, students making the documentary films were at the same time the 'subjects' (agents) and 'objects' (the data) of the learning and the research. Data was captured for discourse analysis in three forms – the documentary films produced by students, uploaded to the project's website and screened at two international film festivals; individual interviews with teachers and group interviews with participating students. The article reviews the discursive data and discusses the potential of this pedagogic intervention for reflexive learning in Citizenship to successfully work in the 'interplay between contexts for action, relationships within and across contexts, and the dispositions that young people bring to such contexts and relationships'.